Surgical management of deep lobe parotid tumours with and without involvement of the parapharyngeal space. Issue 6 (June 2022) - Reerds, S.T.H.; Gerdsen, M.; van den Hoogen, F.J.A.; Takes, R.P.; van den Broek, G.B.; Vallen, H.G.G.J.; Marres, H.A.M.; Honings, J.
Abstract: The diagnosis and treatment of deep lobe parotid tumours is challenging because of the complex surgical accessibility. There is a lack of studies describing the differences between deep lobe tumours that do and do not occupy the parapharyngeal space (PPS). Patients treated for deep lobe tumours occupying the PPS (PPS group) and not occupying the PPS (non-PPS group) were analysed retrospectively. A total of 227 patients were treated surgically for deep lobe parotid tumours between 1990 and 2019. Sixty patients (26.4%) presented with tumours that involved the PPS (PPS group), while 167 (73.6%) presented with tumours that did not occupy the PPS (non-PPS group). The majority of the PPS group tumours were removed using a transcervical or transcervical–transparotid approach. PPS group tumours were larger ( P < 0.001), and tumour spill occurred more frequently in this group (benign tumours: P = 0.002; malignant tumours: P = 0.033). Complication rates did not differ between the PPS and non-PPS groups. A transcervical or transcervical–transparotid approach is the preferred method for the management of deep lobe parotid tumours that occupy the PPS in our practice. Tumour spill occurred more frequently in the PPS group, which is most probably due to the larger tumour size and more complex accessibility.